ANTIBACTERIAL EFFECTIVENESS OF KECAPI LEAF EXTRACT (SANDORICUM KOETJAPE MERR.) ON THE GROWTH OF FUSOBACTERIUM NUCLEATUM (IN VITRO STUDY) - Stefania Valentine Simanjuntak; Yusrinie Wasiaturrahmah; Didit Aspriyanto; Bayu Indra Sukmana; Tri Nurrahman (Universitas Lambung Mangkurat, 2026)
Background: Caries has become one of society's most significant dental health issues, as evidenced by its high prevalence rates. The increased use of antibiotics in dental practice has contributed to the rising antibiotic resistance among oral bacteria. Phytochemical screening of the Sandoricum koetjape leaf extract shows that it contains Flavonoids, Triterpenoids, Alkaloids, Steroids, Saponins, and Phenolics, which have the potential to act as antibacterials from Fusobacterium nucleatum. Purpose: This study aims to analyze the antibacterial effectiveness of kecapi leaf extract (Sandoricum koetjape Merr.) against Fusobacterium nucleatum. Method: This study used an experimental post-test-only control group design consisting of seven treatment groups, namely kecapi leaf extract with a concentration of 30%, 45%, 60%, 75%, 90%, with each group repeated five times. Kruskal Wallis and Post Hoc Mann Whitney tests showed a significant difference in the diameter of the formed inhibition zone. Results:The average diameter of the inhibition zone concentration of 30% was 7,6 mm, 45% was 9,5 mm, 60% was 12,3 mm, 75% was 14,5 mm and 90% was 16,7 mm. Conclusion: Kecapi leaf extract (Sandoricum koetjape Merr.) concentrations of 30%, 45%, 60%, 75%, and 90% have antibacterial potential against the growth of Fusobacterium nucleatum.Keywords : Antibacterial, Fusobacterium nucleatum, Leaf extract, Sandoricum koetjape Merr